Brownish-Yellow Layering on Skin—an Unusual Manifestation of Cutaneous Aspergillosis in a Heart Transplant Recipient - Kiran Gajurel (Annals of Internal Medicine: Clinical Cases)
An unusual cutaneous manifestation of aspergillosis in an immunocompromised patient in which Aspergillus terreus grew on the necrotic skin, creating a brownish-yellow layer of fungal growth, is reported.